Kinetics, Moderators and Reference Limits of Exercise-Induced Elevation of Cardiac Troponin T in Athletes: A Systematic Review and Meta-Analysis - Li, Feifei; Hopkins, Will G.; Wang, Xuejing; Baker, Julien S.; Nie, Jinlei; Qiu, Junqiang; Quach, Binh; Wang, Kun; Yi, Longyan (Frontiers in Physiology, 2021)
Background: Kinetics, moderators and reference limits for exercise-induced cardiac troponin T (cTnT) elevations are still unclear. Methods: A systematic review of published literature was conducted adhering to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. Studies reporting high-sensitivity cardiac troponin T (hs-cTnT) concentrations before and after a bout of exercise in athletes were included and analyzed. The final dataset consisted of 62 estimates from 16 bouts in 13 studies of 5-1002 athletes (1421 in total). Meta-analysis was performed using general linear mixed modelling and Bayesian inferences about effect magnitudes. Modifying fixed-effect moderators of gender, age, baseline level, exercise duration, intensity and modalities were investigated. Simulation was used to derive 99th percentile with 95% limits of upper reference ranges for hs-cTnT of athletic populations. Results: The mean and upper reference limits of hs-cTnT before exercise were 4.4 and 19 ng.L-1. Clear increases in hs-cTnT ranging from large to very large (factor changes of 2.1 to 7.5, 90% compatibility limits, 1.3) were evident from 0.7 through 25 h, peaking at 2.9 h after the midpoint of a 2.5-h bout of running, when the mean and upper reference limit for hs-cTnT were 33 and 390 ng.L-1. A 4-fold increase in exercise duration produced a large clear increase (2.4, 1.7) in post-exercise hs-cTnT. Rowing exercise demonstrated an extremely large clear reduction (0.1 2.4). Conclusions: The kinetics of cTnT elevation following exercise, the positive effect of exercise duration, the impact of exercise modality and 99th upper reference limits for athletic populations were reasonably well defined by this meta-analysis.